Assessment of hydrate formation depth in the oil wells located in permafrost zones - Fedorov, K. M.; Vershinin, V. E.; Khabibullin, R. A.; Varawa, A. I.; Федоров, К. М.; Вершинин, В. Е.; Хабибуллин, Р. А.; Варавва, А. И. (Tyumen State University, 2013)
The paper analyses the influence of oil movement speed on the process of gas hydrate formation in an oil well borehole in the conditions of intensive cooling by means of heat exchange with long-term permafrost soils as exemplified by the Paiyakhskoe field. The mathematical model of non-isothermal oil flow with dissolved gas in a vertical oil well borehole is considered. A simplifying assumption is temperature constancy of soils around the oil well. Analytical dependence of physical oil properties on pressure and temperature was used in numerical calculation of the oil flow parameters. The assessment of hydrate formation conditions was carried out by the VNIIGAZ method. The offered calculation methodology of P-T conditions in the oil well borehole is formulated as a numerical algorithm. The results of numerical calculations of pressure, temperature and hydrate formation depth are demonstrated by means of graphs. The analysis of the resιdts of thermal and hydraulic calculations for oil flow in an oil well borehole allowed to define hydrate free oil production regimes and predictable depths of initial hydrate formation. It has been demonstrated that when a well bore passes through permafrost layers with a low speed of oil flow, favourable conditions for gas hydrate formation appear. Исследовано влияние скорости движения нефти на условия образования газогидратов в стволе нефтяной скважины при интенсивном охлаждении продукции за счет теплообмена с многолетнемерзлыми породами на примере Пайяхского месторождения. Рассмотрена математическая модель неизотермического движения нефти с растворенным газом в стволе вертикальной скважины. Упрощающим допущением была стационарность температуры пород, окружающих скважину. Для реализации численного расчета параметров потока были применены аналитические зависимости физических свойств нефти от давления и температуры. Оценка условий начала гидратообразования проводилась по методике ВНИИГАЗа. Предложенная в работе методика расчета термобарических условий в стволе скважины ...